Note from the Editor - Stefan CZARNECKI (Archives of Acoustics)
ARCHIVES of ACOUSTICS is an English version of the quarterly ARCHIWUM AKUSTYKI which has been published in Polish since 1966, apart from a few papers appeared in other foreign languages, only the sum¬maries of individual papers and the figure captions being printed in English.